Can Racial Differences in Cognitive Test Performance Be Reduced by Presenting Problems in a Social Context? - DESHON, Richard P. (Institutional Knowledge at Singapore Management University, 1998)
It is well documented that African Americans tend to score lower on cognitive ability tests than White Americans. The cause of this performance difference is still being hotly debated and actively researched. Recently, J. E. Helms (1992) argued that cognitive ability tests fail to adequately assess African American intelligence because they do not account for the emphasis placed on social relations and the effect of social context on reasoning in the African American culture. To evaluate this argument, racial subgroup performance differences on Wason conditional reasoning items presented in the standard abstract form and in a social relationship form were examined. Contrary to Helms's argument, results indicate that presenting Wason conditional reasoning items in a social context did not reduce the difference between African American and White American Performance.